Novel approach to a severe craniomaxillofacial trauma in a military working dog using a customized 3D-printed mold for printed polymethylmethacrylate (PMMA) plate–a case report - Babenko, Tatiana; Srugo, Itay; Peery, Dana; Kelmer, Efrat; Klainbart, SIgal (Frontiers in Veterinary Science, 2025)
ObjectiveTo describe a novel two-stage surgical approach for managing complex craniomaxillofacial trauma in a military working dog, including the use of an individualized 3D-printed polymethylmethacrylate (PMMA) plate for frontal bone reconstruction.Case summaryA 3-year-old Belgian Malinois sustained severe head trauma during combat. Clinical examination revealed facial deformation, respiratory distress, and neurological signs. computerized tomography (CT) imaging confirmed multiple fractures, including the frontal and nasal bones, cribriform plate, and frontal sinus, with pneumocephalus. A two-stage approach was employed: (1) Initial stabilization, including a tracheostomy to address respiratory issues and manage intracranial pressure, along with surgical debridement and closure of the frontal sinus. (2) Reconstruction using an individualized 3D-PMMA plate using a customized 3D-printed mold to restore frontal bone integrity.New or unique information providedThis report presents a novel approach to managing complex craniomaxillofacial trauma in dogs, particularly those involving extensive frontal sinus and nasal bone fractures with intracranial complications. The use of an individualized 3D- PMMA plate for frontal bone reconstruction represents a significant advancement in veterinary CMF trauma management, offering a potential solution for achieving both functional and cosmetic outcomes in challenging cases. This case contributes to the limited existing literature on the management of severe frontal sinus fractures in dogs.